Nova prešerniana - Hladnik, Miran (Slavistična revija, 2016)
Prešernology recently documented two new manuscript versions of Prešeren's poems Dohtar and Slovo od mladosti. The authors describe their discovery and appearance, and present facsimiles of all known versions of the poems and their parallel diplomatic transcription. Near-infrared spectroscopy of paper excluded the possibility of falsification. The paper concludes with the analysis of Prešeren's prosody.
Keywords: "Dohtar"; "Slovo od mladosti"; bližnja infrardeča spektroskopija; datacija; diplomatic edition; diplomatski prepis; manuscript variants; manuscritps; near-infrared spectroscopy; Prešeren, France, 1800-1849; Prešernology; prešernoslovje; prosody; rokopisi; Slovene literature; Slovene poetry; Slovene poets; slovenska književost; slovenska poezija; slovenski pesniki; spectrometric dating; verzologija